PENERAPAN ANALISIS STRATEGI UMKMRUMAH MAKAN MASAKAN PADANG “EPG” DI SOLO RAYA - Latifiana, Dwi; Pardede, Nelson (JURNAL GAUNG INFORMATIKA, 2016)
Small and Medium Micro Enterprises in the city of Surakarta are developing, one of which is engaged in culinary. The culinary business is a very promising businessbecause it can provide more than 50% profit. Surakarta is a culinary city with a variety of foods from all over Indonesia. No exception of typical food from West Sumatra thathas mushroomed in the city of Surakarta and its surroundings. Many Padang restaurants are spread throughout the city of Surakarta and its surroundings. Padangfood is popular because of its distinctive taste and different presentation with food from other regions. In the process of serving using neatly arranged plates and when serving to consumers, the waiter will arrange neatly with his hands. With the many Padang restaurants in Surakarta and the high level of consumer interest in Padang cuisine, the researchers analyzed the UMKM strategy using SWOT analysis, EFE Matrix, IFE Matrix and IE Matrix. EPG Restaurant located in Surakarta is suitable forimplementing management strategies in the form of intensive strategies in the form of market penetration, market development and product development and IntegrationStrategies, namely backward integration, forward integration, and horizontal integration, and the final conclusion is (3) to determine what strategy the right one isused in decision making, then the analysis of Quantitative Strategic Planning Matrix (QSPM) is carried out and the results obtained are choosing a product Developmentstrategy with an alternative total score of 3.88 compared to market penetration with a smaller total alternative score of 3, 76